Emotional Intelligence and Aggressive Behaviors: The Case of Police Offic-ers Frontliners Amid Covid-19 Pandemic - Virtudazo, Teresa Jane J.; Pallega, Rowell B.; Naparota, Leo A. (Future Science / FSH-PH Publications, 2025)
This study aimed to examine the relationship between emotional intelligence and aggressive behaviors among Philippine National Po-lice (PNP) frontliners during the COVID-19 pandemic. The respond-ents included 180 police officers from the Dipolog and Dapitan City Police Stations. Utilizing a descriptive-correlational research design and a quantitative approach, data were gathered through a question-naire checklist and analyzed using frequency counting, percentages, weighted mean, standard deviation, the Mann-Whitney test, Kruskal-Wallis test, and Spearman Rank Order Correlation Coefficient.The findings revealed that police officers exhibited high levels of emo-tional intelligence, including self-awareness, emotion regulation, self-motivation, social awareness, social skills, and receptivity. Emotional intelligence was unaffected by age, sex, or years of experience. Mean-while, the officers demonstrated rare physical aggression but moder-ate levels of verbal, emotional, and hostile aggression, resulting in an overall moderate level of aggression. Aggressive behaviors showed no significant differences based on age or years of experience but var-ied significantly by sex. It means that women often score higher in social awareness and empathy, while men excel in self-confidence or emotion regulation. Moreover, the study identified a marginal but significant positive relationship between emotional intelligence and aggressive behaviors at a medium level. The findings suggest that law enforcement officers should enhance their ability to monitor and manage emotions in themselves and others to guide their actions effectively. It is recommended that police stations in Dipolog and Dapitan establish partnerships with health and social care providers to support staff well-being, manage risks, and address aggressive be-havior incidents through prevention, protection, and treatment strat-egies.